INVESTMENT EVALUATION FOR A SMALL HYDRO POWER PLANT - Klemen Deželak; Katarina Dežan; Jože Pihler; Gorazd Štumberger (Journal of Energy Technology, 2024)
In this paper, the investment evaluation in the process of constructing small hydro power plants is investigated. All calculations are performed for a small 27 kW hydro power plant. Both technical and financial aspects are presented, and all of the major indicators for investment approval are considered. The greatest attention is given to the impact of various financial parameters on the indicators for investment approval or rejection. Within the technical aspect, the main input and output technical parameters are observed. Input parameters include the head, flow, turbine type and generator efficiency, while the output parameters of the calculations include hydro power plant power, capacity factor and delivered energy. Within the financial aspect, the initial and annual costs as parameters of extended financial analysis (inflation, discount rate and credit) are considered in the calculations. In this work, the impact of the above parameters on investment approval, in the sense of indicators such as net present value, internal rate of return and the cumulative cash flow is studied.